Implementing Fish Finder and Fish Aggregator Devices to Enhance Operational Efficiency for Traditional Fishermen in Pondok Nongko Village - Jangka Rulianto; Sevri Ton; Arif Fahmi; Rochmad Eko; Indra Kurniawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Universitas Abdurachman Saleh Situbondo, 2026)
This community service project was conducted in Pondok Nongko Village, Kabat District, Banyuwangi Regency, aimed to enhance the efficiency of traditional fishermen’s fishing operations through the application of fish finder and fish-calling technology. The main challenge faced by local fishermen is the difficulty in quickly and accurately locating fish, which leads to high fuel consumption and low catch productivity. The implementation methods included socialization, training on device usage, field operational assistance, and performance evaluation of the technology. The results show that the application of a fish finder significantly accelerates the identification of fish aggregation points, while the fish-calling device increases the likelihood of attracting fish to the netting area. Field trials demonstrated fuel efficiency improvements of up to 30% and an average catch increase of 25% compared to traditional methods. Furthermore, fishermen’s acceptance level of the technology was relatively high, as it was considered practical, economical, and relevant to their operational needs. Therefore, the implementation of these technologies has strong potential as a sustainable solution to support the welfare improvement of traditional fishermen in Pondok Nongko Village.